An improved zero-voltage zero-current transition boost converter employing L-C-S resonant network - Anandh N; Akhilesh Sharma; Julius Fusic S; Ramesh H (Institute of Advanced Engineering and Science, 2020)
An improved zero-voltage zero-current transition boost converter (IZVZCTBC) is introduced. This converter is basically a fourth-order DC-DC converter wherein a L-C-S (Inductor–Capacitor–Switch) resonant circuit is embedded for soft-switching. L-C-S tank network is the modified version of conventional ZVZCT switch cell. The main feature of L-C-S tank circuit is to enhance the performance of zero-voltage zero-current transition boost converter in terms of eliminating the high current stress, decreasing the switching losses and increasing the efficiency of converter. This converter exhibits both zero-voltage turn on and zero-current turn off switching characteristics based on the gating signals applied to switches. The principle of operation and time domain expressions of IZVZCT boost converter with L-C-S cell are presented. For the closed loop operation, digital controller is designed and the performance of the controller has been validated through simulation for different line and load variations. The mathematical and theoretical analysis is verified accurately by a 12-24 V, 30 W converter through PSIM simulation software and the results ensures that overall efficiency of the converter has improved to 97% along with elimination of current stress.